THE UNCONSCIOUS AND SOCIAL LIFE - Hayes, Grahame (PINS-Psychology in Society, 2026)
An idea like "the unconscious and social life" is simultaneously rather grand(iose) and wide-ranging, and there are at least two reasons for proceeding like this. Firstly, I want to think systematically about some of the potential application of psychoanalytic ideas to the grand or big questions facing us in this country. Given the changes that are taking place, it seems reasonable to ask whether psychoanalysis has any applicability to the (big) questions of social transformation. The second reason relates to thinking about psychoanalysis, or rather psychoanalytic ideas, as part of social theory. This idea would be anathema to two kinds of thinkers: on the one hand psychoanalysts and psychologists who tend to resist the social articulation of ideas that seem (inherently) to reside in some internal theoretical and substantive space; and on the other hand social theorists who tend either towards a social reductionism, or a conflation of conceptions of the individual (and individuality) with idealist and individualist conceptions. So it seems worthwhile to pose the question of whether psychoanalysis can be applied in (a broad) social theory way. This seems a necessary theoretical task (even for psychology) as it is not self evident how psychoanalysis can be part of social theory. It is also a political task given the resistance to so-called Euro-centric theories in this country at the moment. What would we have done if Franz Fanon had not been born in Martinique, or Edward Said in Egypt?!